2015
DOI: 10.1002/2014jd022930
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric responses to oceanic eddies in the Kuroshio Extension region

Abstract: We examined atmospheric responses to 35,000+ oceanic eddies in the Kuroshio Extension region during the period of [2006][2007][2008][2009]. Using satellite data, we showed that cold (warm) eddies cause surface winds to decelerate (accelerate) and reduce (increase) latent and sensible heat fluxes, cloud liquid water, water vapor content, and rain rate; all of these changes are quantified. Both the linear correlation between wind divergence and downwind sea surface temperature (SST) gradient and the corresponden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
105
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(126 citation statements)
references
References 55 publications
18
105
2
1
Order By: Relevance
“…The Kuroshio Extension (KE) region, from Japan eastward to the mid‐Pacific, is one of the two largest eddy kinetic energy (EKE) bands in the northern Pacific Ocean (the other being the subtropical frontal zone; Chow et al, ; Liu et al, ; Qiu & Chen, ; Yang et al, ). Eddy activities in the KE play an important role in the decade variations in the KE system circulation (Qiu & Chen, , ) and air‐sea interaction (Ma et al, ). Ma et al () found that the wind speed is enhanced (weakened) and the precipitation is increased (decreased) with the presence of warm (cold) eddies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kuroshio Extension (KE) region, from Japan eastward to the mid‐Pacific, is one of the two largest eddy kinetic energy (EKE) bands in the northern Pacific Ocean (the other being the subtropical frontal zone; Chow et al, ; Liu et al, ; Qiu & Chen, ; Yang et al, ). Eddy activities in the KE play an important role in the decade variations in the KE system circulation (Qiu & Chen, , ) and air‐sea interaction (Ma et al, ). Ma et al () found that the wind speed is enhanced (weakened) and the precipitation is increased (decreased) with the presence of warm (cold) eddies.…”
Section: Introductionmentioning
confidence: 99%
“…Eddy activities in the KE play an important role in the decade variations in the KE system circulation (Qiu & Chen, , ) and air‐sea interaction (Ma et al, ). Ma et al () found that the wind speed is enhanced (weakened) and the precipitation is increased (decreased) with the presence of warm (cold) eddies. After the Kuroshio Current leaves the Japanese coast, it enters the open ocean where the constraint of topography is lost.…”
Section: Introductionmentioning
confidence: 99%
“…The ocean's mesoscale influence on the atmosphere in the extratropics has been known from observational analyses for some time, both near the surface (e.g., Chelton et al 2004;Xie 2004) and in the free troposphere via precipitation, clouds, and upward winds (e.g., Minobe et al 2008Minobe et al , 2010Tokinaga et al 2009;Frenger et al 2013;J. Ma et al 2015;Smirnov et al 2015).…”
Section: The Global Hydrological Cyclementioning
confidence: 99%
“…Ma et al 2015;Smirnov et al 2015). However, it has required deployment of models with sufficient resolution in both the atmosphere and ocean in order to study and understand such interactions at the process level Chelton and Xie 2010;Kwon et al 2010;J. Ma et al 2015;Ma et al 2017).…”
Section: The Global Hydrological Cyclementioning
confidence: 99%
“…The Kuroshio Extension (KE), with steep sea surface temperature (SST) fronts and pinched‐off mesoscale eddies (Yasuda et al, ), induces rich air‐sea interactions through strong surface heat fluxes (Kelly et al, ; Kwon et al, ; Nonaka & Xie, ; Small et al, ). Cold ocean eddies weaken surface wind speed by suppressing turbulent heating (Park et al, ), resulting in surface wind convergences upwind and divergences downwind, and the opposite patterns hold for warm eddies (Frenger et al, ; J. Ma et al, ). Sugimoto et al () used a regional atmospheric model to indicate that oceanic eddies can possibly affect synoptic atmospheric variability.…”
Section: Introductionmentioning
confidence: 99%